(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
This study aims to describe the ecopedagogy approach in Indonesian history textbooks K-13. This study uses a qualitative method with a descriptive approach. The research subjects were teachers and students of MAN Sumenep. Data collection techniques using observation, interviews, and documentation. The results of the study show that there are basic competencies and materials in textbooks that can be developed through an ecopedagogy approach. The KD are 3.4 class X semester 1, 3.6 class X semester 1, 3.8 class X semester 2, 3.2 class XI semester 1, and 3.8 class XII semester 2. In history learning with an ecopedagogy approach, it is divided into 3 stages, namely planning, process learning, and evaluation of learning. Then there are obstacles faced by teachers when the learning process uses textbooks, namely not all the material in Indonesian history textbooks that can be integrated with ecological issues